Os efeitos da categorização de gênero sobre a empatia e o julgamento moral - Ramos, Renalle Ruana Pessoa (2019)
Studies involving Social Identity Theory have been effective in demonstrating differences in response to varied social situations related to the categorization of a target as an ingroup or outgroup member as an effect of what has been termed the ingroup bias. Once social categorization is recognized as an inescapable phenomenon of social life, in what way does it affect moral decisions in everyday life, considering that moral judgment is based on a justice premise? Through a purpose of investigating morality closer to everyday reality, this study used an adaptation of the classic Heinz’s dilemma aiming to analyze the effects of gender categorization on empathy and moral judgment. For that, a version of the dilemma with a female protagonist was also produced and the situations were applied in 183 participants, 92 women and 91 men, in an experimental factorial 2 (female offender versus male offender) x 2 (female participant versus male participant) between-subjects research design. Response data were collected on situational scales of empathy and moral judgment built for this purpose. Additionally, the potential of dispositional empathy, as measured by the IRI, and of moral development, as measured by DIT-1, were verified as moderators of the response to experimental situations. Although differences in empathy have been reported in the literature as a result of target’s group membership, in the direction of greater empathy by ingroup members, no differences in the empathic response to treatments have been observed by analyzing only the effects of the offender’s sex and participant’s sex manipulations. Likewise, no differences were found in moral judgment either. However, differences based on dispositional measures were observed, that is, when the analysis considered a binary classification of participants in low or high scores in terms of empathy and moral development. With regard to empathy, the effects of the experimental treatment appeared to be associated with the activation of gender stereotypes, resulting in differences in situational empathy as the effect of dispositional empathy for the condition in which male participants evaluated a male offender. Regarding moral development, a tendency to derogate ingroup members with a deviant behavior (black sheep effect) was found, so that a greater negative evaluation of the ingroup offender was observed only in the group of participants with low moral development. Overall, the results suggest some possible distinction in moral experience regarding women and men, due to gender differences in empathy. In any case, the occurrence of bias in moral judgment was not observed primarily associated with empathy, but as an effect of the participants’ moral development itself. These findings highlight the importance of including developmental variables in social psychology investigations, as well as the contribution of low moral development to the perpetuation of certain social problems.